Administrative and supervisory practices of elementary school principals in Bataan as perceived by principals themselves, district supervisors and teachers - Izon, Germiniana 1909 (s.n.], 1967)
With the democratic concept as a frame of reference, this study attempts to evaluate several administrative and supervisory practices of elementary school principals in Bataan. This study also includes the correlation between teachers' and principals' perception, principals' and district supervisors' perception, and teachers' and district supervisors' perceptionon these practices.